2022
DOI: 10.3389/fendo.2022.870054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time-Restricted Feeding on Energy Balance: A Cross-Over Trial in Healthy Subjects

Abstract: Time-restricted feeding (TRF) has been recently reported as an effective dietary intervention for losing body weight, implying a negative energy balance, without restricting nutrient intake. However, the detailed energy balance alteration caused by TRF remains unclear. This study was a randomized controlled clinical trial using a within-subject cross-over design. Twelve healthy, normal-weighted volunteers (age: 24 ± 2.3 years; BMI: 21.9 ± 1.71 kg/m2; 7 females) were studied under a rigorous control for calorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
4
13
2
Order By: Relevance
“…Studies on other versions of TRE report more mixed results. For heart rate, only 1 prior study on TRE reported an improvement [43]. In our per-protocol analysis, eTRE+ER did not improve lipids, systolic blood pressure, or diastolic blood pressure.…”
Section: Sleepcontrasting
confidence: 67%
“…Studies on other versions of TRE report more mixed results. For heart rate, only 1 prior study on TRE reported an improvement [43]. In our per-protocol analysis, eTRE+ER did not improve lipids, systolic blood pressure, or diastolic blood pressure.…”
Section: Sleepcontrasting
confidence: 67%
“…Following the electronic database search and subsequent synthesis of articles ( Fig. 1 ), 71 studies were included in the final review [ 3 , 9 17 , 22 52 , 53 82 ]. Full details of these investigations are provided in the Supporting Information_2 ( https://www.jfda-online.com/journal/vol31/iss2/3/ ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, researchers have employed a variety of sample preparation techniques and equipment calibration processes when undertaking bomb calorimetry for food and beverage energy measurement. These include freeze drying [ 9 ], oven drying (at various temperatures) [ 10 , 11 ], grinding [ 12 ], mixing [ 13 ], combustion of different sample volumes [ 14 , 15 ], and analyses of varying sample sizes [ 16 , 17 ]. The extent to which these different approaches have been used, and their impact on subsequent energy discernment, is yet to be rigorously examined.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, this study reported greater reductions in daily eating windows compared with the studies that prescribed CR + eTRE but showed no effect (4.8‐h/day change in baseline eating window vs. 2.3 h vs. 2.4 h, respectively) [22,24,31]. The extended fasting periods in the CR + TRE conditions may have contributed to greater weight loss through a few potential mechanisms, including increased fat oxidation [20,35], daily energy expenditure [37,38], and/or increased fecal energy loss [34]. Additionally, other studies have found that intermittent energy restriction attenuates the reduction in resting metabolic rate associated with continuous CR [37,38].…”
Section: Discussionmentioning
confidence: 99%